Applying moderate or intense low-oxygen dilution combustion to a co-axial-jet I-shaped recuperative radiant tube for further performance enhancement. (15th March 2019) - Tian, Ye; Zhou, Xiong; Ji, Xuanyu; Bai, Jisong; Yuan, Liang
Abstract: The major aim of the present work is to use the self-made burner with the co-axial jet pattern to achieve the Moderate or Intense Low-oxygen Dilution (MILD) combustion in a I-shaped Recuperative Radiant Tube (RRT) and demonstrate its potentiality and superiority using experiments. For this end, the performances (e.g. uniformity of tube wall temperature as well as NOX emission) should be first explored using the traditional firing (conventional combustion) mode. The conclusions drawn suggest that, despite considerable efforts to burner optimization, it is still relatively difficult to further improve the performances. As a result, we modified the structure of I-shaped RRT to transfer the mode from conventional to MILD combustion and the remarkable upgraded performances are yielded. Moreover, the MILD combustion characteristics are verified to be governed by three critical factors (i.e., the recirculation ratio K A, flue gas temperature T f and oxygen volumetric fraction in oxidizer f O 2 ), and the quantitative relationship between the noted three for establishment conditions are discussed. It is found that, increasing f O 2 from 0.18 to 0.30 makes the prerequisite K A significantly rise from 0.36 to 0.49 and the corresponding T f increase from 994 K to 1341 K, to sustain the MILD combustion mode. Based on the experimental data, the analysis of stability limits suggests the narrowed MILD combustion region with the increase in f O 2, especially at the situation of f O 2 over 0.25. The results obtained overcame the substantial gap between the MILD technology achievement and co-axial-jet pattern in a narrow and small space. Accordingly, the present work seeks to further effectively extend the establishment mechanism of MILD combustion and theoretically guide the parameter optimization of such a common industrial heating item as the I-shaped RRT. Highlights: The experimental study on an I-shaped recuperative radiant tube was conducted. Moderate or Intense Low-oxygen Dilution combustion mode was realized in this tube. The performances were confirmed to be remarkably upgraded under this mode. The quantitative relationship between key factors for mode establishment was revealed. Stability limits analysis for the region of this mode has been done.